(untitled) (مجلة وقف في دراسات الاوقاف, 2026)
In this chapter, the researcher presents the proposed framework for the current study, focusing on the general goal of establishing practical mechanisms to achieve financial sustainability for the endowments of Saudi universities. Additionally, the chapter provides a summary of the study’s results, key related recommendations, and some suggestions for future research.